Experience and Discussion: Safeguards for People With Disabilities During the COVID-19 Pandemic in China - Qi, Fei; Wu, Yuqi; Wang, Qi (Frontiers in Public Health, 2021)
The special vulnerability of people with disability (PWD) in the COIVD-19 pandemic has been confirmed by many studies, but data shows that the infection rate of PWD in China is lower than for non-disabled people. We believe that this difference can be attributed to the Chinese government's targeted safeguards for the disabled community during the pandemic, including support for disability empowerment, the establishment of a remote interactive decision-making system, fair vaccine distribution and economic protection for PWD. The professionalism of decision-makers and the maintenance of channels of interaction with PWD are also important. All of these changes have benefitted China's public health policy and legal framework. This system, which has six components (governance, prevention, response, knowledge, coordination, and people), enables the country to quickly formulate a series of safeguards for PWD that have a sufficient legal basis. We believe that China's rapidly improving public health policy and legal framework will make a hugely significant impact by alleviating the impact of the COVID-19 pandemic on the PWD community. Countries should pay more attention to discovering the special needs and obstacles of PWD in the COIVD-19 pandemic: in referring to China's experience, they should explore the protection framework for persons with disabilities and adjust it to their own needs on the basis of national conditions.